Ketimpangan Fasilitas, Proses be Ketimpangan Fasilitas Pembelajaran Terhadap Proses Belajar Madrasah di Pasuruan: - - fahira, firda umi (Maliki Interdisciplinary Journal, 2025)
Disparities in learning facilities represent a crucial issue in the field of education, directly affecting the quality of the teaching and learning process as well as student learning outcomes. This study aims to examine the impact of unequal learning facilities on students’ learning processes at MAN 1 Pasuruan. In the context of a rapidly evolving era that demands innovation and effectiveness in education, the availability of adequate facilities has become an essential factor that cannot be overlooked. This research employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The research subjects consist of 10th and 11th-grade students as well as several teachers from various subjects, selected purposively based on the differing conditions of facilities in each classroom.The findings reveal that only a small number of classrooms are equipped with complete learning facilities such as projectors, computers, and stable internet connections. This disparity directly impacts the teaching methods employed by teachers, student engagement in class, and their academic achievements. Students in well-equipped classrooms demonstrate higher levels of participation and understanding compared to those in poorly equipped classes. Teachers also face challenges in applying innovative teaching methods in classrooms with limited facilities, resulting in lower job satisfaction and higher stress levels. This inequality further risks widening the gap in access to essential learning skills such as critical thinking, communication abilities, and mastery of educational technologies—skills that are increasingly important in the modern era. These findings underscore the importance of equitable distribution of educational facilities to achieve fair and equal learning access for all students.